2010
DOI: 10.1007/s11109-010-9125-x
|View full text |Cite
|
Sign up to set email alerts
|

Timing Is Everything? Primacy and Recency Effects in Voter Mobilization Campaigns

Abstract: The timing of message delivery in political campaigns is a key component of strategy. Yet studies that examine the impact of message timing on political behavior are surprisingly rare. Although one recent study finds that appeals delivered closer to Election Day will be most effective (Nickerson, American Journal of Political Science 51 (2): [269][270][271][272][273][274][275][276][277][278][279][280][281][282] 2007), methodological considerations render this conclusion tentative and suggest the impact of mess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 20 publications
2
33
2
Order By: Relevance
“…First, we add to the mobilization literature on the effectiveness of GOTV techniques. In recent years, there has been a surge in field experiments testing various mobilization methods (Abrajano and Panagopoulos 2011 ;Garcia Bedolla and Michelson 2012;Gerber and Green 2000;Gerber, Green, and Larimer 2008;Green and Gerber 2008;Green, Gerber, and Nickerson 2003;Michelson 2003Michelson , 2006Michelson, Garcia Bedolla, and McConncU 2009;Nickerson 2008;Panagopoulos 2010Panagopoulos , 2011. While these studies provide evidence that GOTV tools can increase tumout, our knowledge remains incomplete conceming tmder which conditions these mechanisms work.…”
mentioning
confidence: 99%
“…First, we add to the mobilization literature on the effectiveness of GOTV techniques. In recent years, there has been a surge in field experiments testing various mobilization methods (Abrajano and Panagopoulos 2011 ;Garcia Bedolla and Michelson 2012;Gerber and Green 2000;Gerber, Green, and Larimer 2008;Green and Gerber 2008;Green, Gerber, and Nickerson 2003;Michelson 2003Michelson , 2006Michelson, Garcia Bedolla, and McConncU 2009;Nickerson 2008;Panagopoulos 2010Panagopoulos , 2011. While these studies provide evidence that GOTV tools can increase tumout, our knowledge remains incomplete conceming tmder which conditions these mechanisms work.…”
mentioning
confidence: 99%
“…Research on primacy effects maintains that information presented first has a stronger effect on judgments and is more likely to change an individual’s judgment than information that is presented last [30, 31]. On the other hand, other researchers have found a recency effect, which suggests that information presented last has a stronger effect than the information that is presented first [32, 33]. Though the evidence is contradictory, both the primacy and the recency effects demonstrate the power of serial positioning effects.…”
Section: Presentation Order and Justice Evaluationsmentioning
confidence: 99%
“…Much work has been done examining how people react to multiple events or items. Examples include advertising [14] (i.e., which commercials people remember most strongly) and political campaigns [13] (i.e., what timing and content of campaign messages resonate most with potential voters). We could not find any studies that analyze how individuals react, process, and remember multiple traumatic or violent events.…”
Section: Setting and Assumptionsmentioning
confidence: 99%
“…This behavioral pattern is consistent with the results in [3] that found that a side was ''punished'' immediately after causing collateral casualties, but then, after a few weeks, the disadvantage faced by the responsible side disappeared. While we model the general case where individuals transit from an insensitive stage back to a sensitive stage, we only analyze the two extreme cases, sometimes called in the literature of behavioral psychology Primacy and Recency (see e.g., [10,13]). Primacy means that the first experience to some stimulus shapes the behavior of an individual and therefore the transition is always one way: sensitive (to the stimulus) to insensitive.…”
Section: Setting and Assumptionsmentioning
confidence: 99%